ANALISIS PERBANDINGAN UPAH BURUH PERTANIAN DAN NON PERTANIAN DI DESA SALO TIMUR KECAMATAN SALO - Ridho Amimi; Harlen '; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted to determine the difference between the wage rates of agricultural laborers with non-agricultural workers and to determine the effect of wages on the welfare of farm and non-farm labor. This research was conducted with descriptive and quantitative method that uses primary data and secondary data obtained through interviews / interview and questionnaire study. Respondents were taken was 50 of 28 farm workers and 22 non-agricultural workers.From the results of this study concluded there are significant differences between the level of wages of agricultural laborers with non-agricultural wage rate. where the average income - average which can be obtained by nonagricultural workers are not the same as agricultural laborers. With the high level of wages will be able to improve the welfare of workers that will increase labor productivity. Based on the results of this research is that many agricultural workers are still less prosperous. With the welfare of the workers are fulfilled, then the labor productivity will also increase. Therefore, the company should increase the level of wages that will improve the welfare of workers as well. Therefore, the authors suggest Need for guidance and provision of appropriate skills for workers in agriculture, so that workers will get better wages for the workers already have the skills.Keywords: Wages, Agriculture, Comparative Analysis